The Effect of Cooperative Integrated Reading and Composition (CIRC) Technique on the Students' Reading Skill at UTM Mataram - Lalu Isnaeni Rahman (Muhammadiyah University of Mataram, 2020)
ABSTRACTThe study aimed to determine the effect of using the Cooperative Integrated Reading and Composition (CIRC) Method on the reading skills of students at UTM Mataram. The method used in this study was a quasi-experimental research design in which the researcher placed two different groups and gave them different treatments. The sampling technique used random sampling with a total of 20 students. The research instrument used pre-test and post-test. The data analysis technique used a t-test. And the research result is that there is a positive and significant effect. The experimental group of this study was taught using the Cooperative Integrated Reading and Composition (CIRC) Method, while the control group of the study was taught using the conventional reading method. The results of the pretest and posttest were found to be satisfactory with the level of achievement of the median homogeneity of 0.449> 0.05, the normality test of 0.715 greater than 0.05, and the results of the t-calculation to determine the effectiveness of the CIRC Method of 0.449> 0.05, which shows that this method was able to boost the effectiveness of student learning. At the end of this study, hopefully, the results of this study can benefit all education stakeholders such as teachers, students, scholars, and even other researchers to support them in creating and analyzing creative and innovative language teaching methods. The researcher expects that the findings of this research can provide some evidence about cooperative language teaching, in this case, the CIRC Method to support the improvement of the teaching and language learning process at UTM Mataram in particular.